Fibrous Dysplasia of Jaws - Eight Case Reports with Review of Literature - Shilpa J Parikh; Shweta Goel; Sonal Thakkar; Parita K Chitroda (Wolters Kluwer Medknow Publications, 2006)
The difficult problem of diagnosis in fibrous dysplasia is well recognised. A clear-cut diagnosis can seldom be made on the basis of clinical, radiological or histological examination alone. Although the usefulness of radiographic examination in the diagnosis of fibrous dysplasia of the skull and facial bones have been highlighted. Histologic and radiographic findings do not always correspond. The radiograph does, however, define the limits and characteristics of the condition grossly. Some of the radiographic features of this disease are sufficiently characteristic as to appear at tunes to be diagnostic.